FORMATION OF ENTREPRENEURIAL COMPETENCE OF GENERAL SECONDARY EDUCATION ACCESSORIES: FOREIGN EXPERIENCE - Zavgorodnia, Tetiana (Mountain School of Ukrainian Carpaty, 2020)
The article analyzes the scientific achievements of domestic and foreign researchers on the problem of formation of entrepreneurial competence of the individual, in particular students; the essence of this definition, its criteria and indicators are revealed, the experience of formation of entrepreneurial competence in applicants for general secondary education institutions of foreign countries is described. The results of the analysis of psychological and pedagogical works showed that a significant place in modern education is given to the study of competency approach in secondary schools, attempts to identify basic competencies in educational programs as a guide to determine the scientific and methodological quality of graduate training. The refore, today the work of domestic and foreign scientists (M. Albert, D. Adamson, E. Bobinskaya, S. Bondar, I. Galyamina, P.Drucker, S. Goncharenko, M. Crane, S. Klepko, T. Matveeva, G. Nazarenko, O.Protsenko, K. Randall, M. Romanova, O. Romanovsky, G. Selevko, O. Sulaeva, J.Tatur, M. Tovkalo, S. Shishov, D. Shepherd, R. Shiyan, V. Yagupov and others). It is noted that the successful solution of this problem is facilitated by the development at the EU and individual countries of the regulatory framework; transition of school education to the competence model; saturation of the content of educational disciplines and forms of education with material that will make it possible to better prepare the future generation for further life, to form the personalities of future creative entrepreneurs; realization of the integral, complex creative approach of the teacher to the organization and carrying out of processes of training and education, the account of age and personal features of pupils. The problem of competence approach to general secondary education is relevant worldwide, and its successful solution will better prepare the next generation for further life, to form a graduate's critical thinking, willingness to innovate, communication skills and ability to work in a team, and thus successfully build your own career. Further research is required (among other things) to prepare future teachers for the formation of entrepreneurial competence of students in secondary schools.